Traffic-Related Air Pollution and Otitis Media - Michael Bräuer; Ulrike Gehring; Bert Brunekreef; Johan de Jongste; Jorrit Gerritsen; Maroeska M. Rovers; H.-Erich Wichmann; Alet H. Wijga; Joachim Heinrich (2006)
BackgroundOtitis media is one of the most common infections in young children. Although exposure to environmental tobacco smoke is a known risk factor associated with otitis media, little information is available regarding the potential association with air pollution.ObjectiveWe set out to study the relationship between exposure to traffic-related air pollution and otitis media in two birth cohorts.MethodsIndividual estimates of outdoor concentrations of traffic-related air pollutants—nitrogen dioxide, fine particles [particulate matter with aerodynamic diameters ≤ 2.5 μm (PM2.5)], and elemental carbon—were calculated for home addresses of approximately 3,700 and 650 infants from birth cohort studies in the Netherlands and Germany, respectively. Air pollution exposure was analyzed in relation to physician diagnosis of otitis media in the first 2 years of life.ResultsOdds ratios (adjusted for known major risk factors) for otitis media indicated positive associations with traffic-related air pollutants. An increase in 3 μg/m3 PM2.5, 0.5 μg/m3 elemental carbon, and 10 μg/m3 NO2 was associated with odds ratios of 1.13 (95% confidence interval, 1.00–1.27), 1.10 (1.00–1.22), and 1.14 (1.03–1.27) in the Netherlands and 1.24 (0.84–1.83), 1.10 (0.86–1.41), and 1.14 (0.87–1.49) in Germany, respectively.ConclusionsThese findings indicate an association between exposure to traffic-related air pollutants and the incidence of otitis media. Given the ubiquitous nature of air pollution exposure and the importance of otitis media to children's health, these findings have significant public health implications.